2018
DOI: 10.4269/ajtmh.17-0231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Malaria Urban Risk Using an Immuno-Epidemiological Biomarker of Human Exposure to Anopheles Bites

Abstract: Urban malaria is an underestimated serious health concern in African countries. This study aimed to evaluate the risk of malaria transmission in an urban area by evaluating the level of human exposure to bites using an salivary biomarker ( Salivary Gland Protein-6 peptide 1 [gSG6-P1] peptide). Two multidisciplinary cross-sectional studies were undertaken in five sites of Bouaké city (three urban districts and two surrounding villages, used as control; Côte d'Ivoire) during the rainy season and the dry season. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 25 publications
5
24
2
Order By: Relevance
“…Anopheles classically like small, open, sunlit, fresh stagnant water suggesting a mosaic of isolated pockets of Anopheles breeding sites in the urban context that may result of local hot spots of Anopheles exposure that could not have been identified. As mentioned above, the use of vector control strategies and/or sociological factors specific to the urban context may also explain the discrepancies observed between the two approaches [39]. Parasitological data indicated that Plasmodium prevalence and density (the gold standard to measure the transmission of malaria) were similar between the two sites, thereby suggesting that children were exposed similarly to malaria transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anopheles classically like small, open, sunlit, fresh stagnant water suggesting a mosaic of isolated pockets of Anopheles breeding sites in the urban context that may result of local hot spots of Anopheles exposure that could not have been identified. As mentioned above, the use of vector control strategies and/or sociological factors specific to the urban context may also explain the discrepancies observed between the two approaches [39]. Parasitological data indicated that Plasmodium prevalence and density (the gold standard to measure the transmission of malaria) were similar between the two sites, thereby suggesting that children were exposed similarly to malaria transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in Bouaké (7° 69 N, 5° 03 W) located in the centre of Côte d'Ivoire. The study area, study design, and local malaria epidemiology have been previously described in detail [39]. Briefly, the climate is tropical humid with two seasons: the dry season runs from November through March, and the rainy season occurs from April to October.…”
Section: Study Sites and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibody titers to mosquito saliva are a proxy for the intensity of mosquito bites received by the individual. This biomarker has been used to assess the risk of malaria transmission in low-level exposure/transmission areas to accurately evaluate the effectiveness of interventions [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%